(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In the Untermann’s Corpus the graffiti G.9.5 was advertised as incompleted. But few years ago was found the missing half to the piece, with graffiti too. In the editio princeps of the whole object the reading of both graffitis is advertised as only one. However there are any details that make think that they are two different graffitis, readed in 180º from each other.